(untitled) (Research, Society and Development, 2024)
Introduction: Gut-brain communication plays an important role in understanding the complex etiology of depression, offering insights into new therapeutic avenues. Objective: The objective of this review is to evaluate the role of the intestinal microbiota in cases of depression. Methodology: A review of academic literature indexed in national and international databases was carried out using a scoping review methodology. Data sources used included PubMed, Lilacs and Google Scholar. The keywords "Gut Microbiota" AND "Depression" were used for the search. Results: Of the 975 articles found, 943 were excluded based on titles and abstracts, 18 articles were excluded after complete reading and 14 were included. Conclusions: These findings suggest that several taxa and their mechanisms of action may play a role in the pathophysiology of depression, involving the communication of peripheral inflammation with the brain.